American foreign policy at the crossroads: Between idealism and realism, informal and formal empire, unilateralism and multilateralism - Vuković Milovan (Međunarodni Problemi, 2004)
This article compares and contrasts current U.S. "war on terrorism" and proliferation of nuclear, chemical, and biological weapons (NBC’s) with the general U.S. foreign policy during the Cold-War and post-Cold War eras. The focus is primarily on a growing dilemma - "informal" or "formal" American empire - that rises from unprecedented asymmetry in military power between the United States and its closest followers. Also, this article analyzes the role of non-material elements of power (so-called soft power) and reviews recent views regarding the "unilateralism-multilateralism dichotomy" in American foreign policy. The author demonstrates that the "war on terrorism" and proliferation of NBC’s weapons show that U.S. status as the only super-power is not simply a matter of resource availability and relative power. Military muscle is an essential requirement, but it does not itself secure that position. This is especially true for the status of an empire either "informal" or "formal.".